Foucaultian Genealogy and dissident artistic practices: a new look at part of Artivist Brenda Bazante production: um reolhar sobre parte da produção da Artivista Brenda Bazante (Revista Apotheke, 2021)
In this article i try to understand how i woke up to the need to combine artistic practices and transfeminist activism, reinforcing the artivist vanguard that works from themes related to gender disobedience. For that, i took a new look at my production in the visual field, using Foucault´s Genealogy as a methodological path. In this path, i re-observed records of performances, sculptures, modeling and educational activities carried out between the years 2014 and 2020. In the review described here, i mainly points out flashes and traces of artistic actions/gestures that indicated the presence of critical postures related to political, social issues, artivist and gender dissident. The theoretical panorama was formed by Foucault (1979), Rancière (2012), Butler (2020), Preciado (2017), Bento (2006), Jesus (2014) and others. Finally, i consider that understanding of transsexual experience will occur moreeasily if its studied and represented by means of different field of knowledge, including art education. Understanding that will be enhanced in direct contact with the public, either through artistic activities that contain the trans theme or by the simple presence of a trans person proposing such actions. In addition, i notice that my artivism stance was gradually created with each action. It was born in the bowels of disobedient practices that i performed and today it extrapolates the pores of my artistic works.